Female sexual hormones and their relationship with periodontal disease - Martha Elena Fajardo Puig; Oscar Rodríguez Reyes; Acela Rodríguez Bacallao (Centro Provincial de Información de Ciencias Médicas, 2017)
Female sexual hormones besides playing an important role in the reproductive endocrinology, regulate diverse tissue functions. In presence of dental plaque (biofilm) associated to inflammatory changes, these hormones influence in the beginning and progress of periodontal disease. In this study the current morphofunctional and pathophysiological aspects related to that thematic are exposed, with the purpose of increasing the knowledge level of dentists and in this way improving the quality of care offered to patients.